Wastes Management Can Minimize CH4 and N2O Emissions from Wetlands in Indonesia - Abdul Hadi; U Udiantoro; Abrani Sulaiman; Hasrul Satria Noor; T Taufiqurrahman; Abdul Ghafur; Rosenani Abu Bakar (Journal of Wetlands Environmental Management, 2015)
Paddy (Oriza sativa L.) and Oil palm (Elaeis guineensis Jack) are two important crops and are potential toproduce wastes which may lead to huge green house gas emissions if they are not managed properly. Openburning and conventional composting are commonly practiced by farmers and/or planters to managedagricultural wastes in Indonesia. A series of research has been carried out to elucidate (1) the reductions ofCH4 and N2O due to incertion of a catalitic converter on burning kiln, (2) green house gas emissions fromdifferent composting techniques of oil palm field wastes, and (3) the effects of oil palm field wastes compostapplication in oil palm fields and of paddy field wastes biochar in integrated oil palm-paddy fields. Theresults showed that CH4 and N2O emissions from paddy field wastes (i.e., rice straw or rice husk) was lowerthan that from oil palm empty fruit bunch (EFB). Furthermore, insertion of a catalytic converter intopyrolysis installation reduced the CO2, CH4 and N2O emissions from paddy field wastes as much as 14.5,17.8 and 11.1%, respectively. Incorporation of EFB compost did not increase greenhouse gas emission fromoil palm fields. These results suggest that biochar and EFB compost can be practiced to manage agriculturalwastes in Indonesia.